Integrated Marketing Communication Strategy For Cannon Viking: Case Study Of Cannon Far East Indonesia - Kemas Rahmat Zen Vani (UniSadhuGuna Business School, 2024)
Cannon Far East Indonesia (CFEI) is one of the market leaders for PU (polyutherane) processing machine providers in Indonesia. However, in bedding and mattress PU application, CFEI encounters difficulties in selling Cannon Viking machines which negatively affects CFEI sales in Indonesia. Even with economic recovery post-pandemic, CFEI’s position in the bedding and mattress market does not seem to change significantly, in comparison to the growth of the processing industry in Indonesia. Hence, the brand awareness issue of CFEI’s Cannon Viking machines is to be explored further in this research, as well as its impact on consumer’s purchase intention. This research contributes to the analysis of the bedding and mattress market of PU applications in Indonesia, as well as the factors impacting customer purchase intention within the industry. The objectives of this research are to conduct internal and external analysis of CFEI, identify factors influencing purchase intentions for consumers, and create promotion strategies to increase the brand awareness of CFEI’s Cannon Viking products. This research utilizes qualitative methodology for data collection and hypothesis analysis. The research data are collected using observation of CFEI’s operations, questionnaire distributions, and interviews with CFEI’s customers. The external analysis was conducted using PESTEL Analysis, Porter’s Five Forces, Competitor and Customer Analysis, while the internal analysis was conducted using VRIO, Marketing Mix, STP Analysis, and Value Chain Analysis. The result of the research shows that IMC affects both Brand Awareness and Consumer Perception, which also affect Purchase Intention respectively. CFEI is recommended to implement the IMC plan with a stronger emphasis on the strength of Cannon Viking machines and initiate digital marketing activities to form a stronger online presence in Indonesia.